2017
DOI: 10.1007/s10479-017-2511-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sample size and order size in an inventory model with quality inspection and return of defective items

Abstract: To ensure all products as perfect, inspection is essential, even though it is not possible to inspect all products after producing them like some special type products as plastic joint for the water pipe. In this direction, this paper develops an inventory model with lot inspection policy. With the help of lot inspection, all products need not to be verified still the retailer can decide the quality of products during inspection. If retailer founds products as imperfect quality, the products are sent back to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…[24] examined optimal inspection-based preventive maintenance policy for three-state mechanical components under competing failure modes. [25] developed an inventory model with lot inspection-based policy and found that optimal order size and sample size were intrinsically linked and maximize the total profit. Different from the aforementioned previous studies, we contribute to this line of research by modelling the quality improvement incentives under uncertainty theory rather than probability theory, as none of supply chain members' effort choices is observable while there is information asymmetry with regards to the supplier's inherent quality level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[24] examined optimal inspection-based preventive maintenance policy for three-state mechanical components under competing failure modes. [25] developed an inventory model with lot inspection-based policy and found that optimal order size and sample size were intrinsically linked and maximize the total profit. Different from the aforementioned previous studies, we contribute to this line of research by modelling the quality improvement incentives under uncertainty theory rather than probability theory, as none of supply chain members' effort choices is observable while there is information asymmetry with regards to the supplier's inherent quality level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comprehensive literature review can be found in Sarkar and Saren (2016). Cheikhrouhou et al (2018) also consider lot inspection policy instead of full. Inspection errors are also considered in the model and the consequence of these errors is dealt in two ways.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The work of Eben-Chaime [14] is, perhaps the first step in this direction (and note the difference between the analysis in [14] and the incomplete/imperfect analysis in Appendix A of [6]), but even in this work inspections and inspection errors are disregarded. A common method for coping with defective items is to make inspections (e.g., [15][16][17][18][19]). Nevertheless, focusing on quality, most studies on inspections (e.g., [17][18][19]) concentrate on error type IImissed defective units, while taking no notice of the waste which is associated with type I errors -false rejections.…”
Section: Literature Surveymentioning
confidence: 99%
“…A common method for coping with defective items is to make inspections (e.g., [15][16][17][18][19]). Nevertheless, focusing on quality, most studies on inspections (e.g., [17][18][19]) concentrate on error type IImissed defective units, while taking no notice of the waste which is associated with type I errors -false rejections. Very few studies, if any, consider assembly system quality with inspections and inspection errors of both types.…”
Section: Literature Surveymentioning
confidence: 99%